Linking Molecular Classification of Hepatocellular Carcinoma and Personalized Medicine: Preliminary Steps - Villanueva, Augusto (2008)
Recent advances have improved our understanding of the molecular pathogenesis of hepatocellular carcinoma (HCC). The development of high-throughput technologies able to simultaneously investigate thousands of genes (SNP-array, gene expression microarray, etc.) has opened a new era in translational research. However, obtaining a molecular classification of HCC remains a striking challenge. Different investigators attempted to classify patients according to their liver cancer molecular background, a feature that will path the way for trial enrichment and personalized medicine. Currently, HCC can be classified in molecular classes according to Wnt-βcatenin pathway activation, proliferation signature activation (associated with chromosomal instability), and other subgroups. In parallel, the first-time ever positive results of a phase III trial in advanced HCC with the multikinase inhibitor sorafenib have encouraged this approach. The current review summarizes the molecular classifications of HCC reported, analyzes the status of targeted therapies tested in clinical trials, and evaluates feasibility of personalized medicine approaches in HCC.